Bayesian Geographically Weighted Generalized Poisson Regression Modeling on Maternal Mortality in NTT in 2022 - Wijaya, Dewi Ratnasari; Pramoedyo, Henny; Suryawardhani, Ni Wayan (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2025)
Maternal mortality is a crucial indicator of healthcare quality, particularly in East Nusa Tenggara (NTT) Province, which still records high mortality rates with significant spatial variation. This study aims to model maternal mortality in NTT in 2022 using the Bayesian Geographically Weighted Generalized Poisson Regression (BGWGPR) approach. This method integrates spatial weighting techniques with Bayesian parameter estimation through Gibbs Sampling to address spatial data characterized by overdispersion. Significant factors, including pregnant women's visits to healthcare facilities (K1), were found to influence the distribution of maternal deaths across districts in NTT. The model identifies that visits to healthcare facilities (K1) (X_1) are significant across all regions, while the variable for pregnant women receiving Tetanus Toxoid (X_3) is only significant in Alor and Timor Tengah Selatan. This model not only provides insights into determining factors but also helps identify priority areas for intervention. Therefore, this study contributes to evidence-based health policy-making aimed at reducing maternal mortality in NTT. The BGWGPR approach proves to be relevant for analyzing complex spatial data and can be applied to other epidemiological cases.